Perbandingan Efektivitas Kombinasi Gabapentin-Ondansetron dengan Dexamethasone-Ondansetron sebagai Profilaksis Postoperative Nausea-Vomiting (PONV) pada Operasi Laparoskopi - Ridha, Ihsanur; Wisudarti, Calcarina Fitriani Retno; Kurniawaty, Juni (Jurnal Komplikasi Anestesi, 2021)
Background: Post Operative Nausea and Vomiting (PONV) is a complication that most often occurs in patients undergoing surgery under general anesthesia, with an incidence rate of 40-90%. The existing combination drug guidelines to prevent PONV have not been effective in significantly reducing the incidence of PONV. There are several research results that suggest that the GabapentinOndansetron combination is effective in reducing the incidence of PONV. Objective: This study aims to compare the effectiveness of the combination of Gabapentin-Ondansetron with Dexamethasone-Ondansetron as a prophylactic of Post Operative Nausea and Vomiting (PONV) in laparoscopic surgery. Methods: This study is a double-blind Randomized Controlled Trial/RCT involving 78 patients who underwent a laparoscopic procedure. Subjects were divided into two groups A and B. Group A was given a combination of Gabapentin 600 mg and Ondansetron 0.1 mg/kgBW. Group B was given a combination of Dexamethasone 10 mg and Ondansetron 0.1 mg/kgBW. Both groups assessed the incidence of PONV using VNRS for nausea and assessed the presence or absence of vomiting. Results: At 15 and 30 minutes postoperatively, Gabapentin-Ondansetron was better than Dexamethasone-Ondansetron as a prophylactic of nausea (p <0.05) in laparoscopic surgery. At 60, 90, and 24 hours postoperatively, the drug combination of the two groups was as good as nausea prophylaxis (p >0.05) for laparoscopic surgery. Both of these drug combinations had the same effect as vomiting prophylaxis (p >0.05) after laparoscopic surgery. Conclusion: Gabapentin-Ondansetron combination is more effective thanDexamethasone-Ondansetron combination as a prophylactic of Post OperativeNausea and Vomiting (PONV) in laparoscopic surgery